2018
DOI: 10.21037/jtd.2018.07.12
|View full text |Cite
|
Sign up to set email alerts
|

Does age over 80 years have to be a contraindication for lung cancer surgery—a nationwide database study

Abstract: Concerning IHM, age ≥80 had a lower weight than did a previous pulmonary or liver disease and the type of pulmonary resection. Patients over 80s with localized LC and no significant comorbidities should be referred for surgery if lobectomy or sublobar resection could be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Another French paper which analysed the administrative database [14], showed a crude 30-day mortality rate of 3.85% for octogenarians operated with VATS approach, while with the traditional thoracotomic approach the 30-day mortality rate was 7.9% (p < 0.0001). A more recent paper by the same authors confirmed a higher mortality rate for octogenarians (7.77% vs 3.54%) and also the association between post-operative death and comorbidities and type of surgical resection: pneumonectomy and bilobectomy had higher rates of mortality and significative higher values of OR (3.83 and 2.18, respectively) [15]. Bravo Iniguez [16] compared the post-operative outcomes of lobectomy for NSCLC in elderly patients (>65 years) analysing the ACS-NSQIP database: 30-day mortality was significantly lower for VATS-lobectomy (1.19%) than open lobectomy (3.13%) without a significant increased risk of death for patients aged 75-80 years.…”
Section: Discussionmentioning
confidence: 76%
“…Another French paper which analysed the administrative database [14], showed a crude 30-day mortality rate of 3.85% for octogenarians operated with VATS approach, while with the traditional thoracotomic approach the 30-day mortality rate was 7.9% (p < 0.0001). A more recent paper by the same authors confirmed a higher mortality rate for octogenarians (7.77% vs 3.54%) and also the association between post-operative death and comorbidities and type of surgical resection: pneumonectomy and bilobectomy had higher rates of mortality and significative higher values of OR (3.83 and 2.18, respectively) [15]. Bravo Iniguez [16] compared the post-operative outcomes of lobectomy for NSCLC in elderly patients (>65 years) analysing the ACS-NSQIP database: 30-day mortality was significantly lower for VATS-lobectomy (1.19%) than open lobectomy (3.13%) without a significant increased risk of death for patients aged 75-80 years.…”
Section: Discussionmentioning
confidence: 76%
“…It provides a huge amount of epidemiological information about hospitalized French patients [26][27][28][29][30][31]. Moreover, data pertaining to pulmonary resection for LC are reliable enough to count such patients, as previously shown in other studies [32][33][34][35][36][37].…”
Section: Limitations and Strengthsmentioning
confidence: 75%
“…[9][10][11] Moreover, data pertaining to pulmonary resection for lung cancer are reliable enough to count such patients, as previously shown in other studies. [20][21][22][23][24] The authorisations required by the 'Cancer Plan' from 2009 onwards have resulted in fewer hospitals performing lung resections for cancer, going from 253 in 2005 to 146 in 2020. However, this number remains high if we compare it to other comparable countries such as England.…”
Section: Discussionmentioning
confidence: 99%